2019
DOI: 10.1016/j.juro.2018.08.044
|View full text |Cite
|
Sign up to set email alerts
|

International Multicenter Validation of an Intermediate Risk Subclassification of Prostate Cancer Managed with Radical Treatment without Hormone Therapy

Abstract: This multicenter international effort independently validates the prognostic value of the IR-PCa subclassification in ADT-naïve patients across all radical treatment modalities. It is unlikely that treatment intensification will meaningfully improve oncologic outcomes for FIR men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 1 publication
2
15
0
2
Order By: Relevance
“…Although AS was not explored in that study, it showed a starkly higher risk of metastasis at 10 years in men with CPG3 disease (10-13.5%) than those with CPG2 (0.2-3.5%) depending on the type of radical treatment. That study [30] also, unsurprisingly, showed very different rates of PCM, with results remarkably similar to our own present findings. Based on this, it would seem reasonable that progression to CPG3 is a pragmatic trigger to end AS and switch to treatment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although AS was not explored in that study, it showed a starkly higher risk of metastasis at 10 years in men with CPG3 disease (10-13.5%) than those with CPG2 (0.2-3.5%) depending on the type of radical treatment. That study [30] also, unsurprisingly, showed very different rates of PCM, with results remarkably similar to our own present findings. Based on this, it would seem reasonable that progression to CPG3 is a pragmatic trigger to end AS and switch to treatment.…”
Section: Discussionsupporting
confidence: 92%
“…They are also consistent with results from the randomised Prostate Testing for Cancer and Treatment (ProtecT) trial and other studies whereby the majority of men had low‐ or favourable intermediate‐risk disease without survival differences between treated and untreated men . While the present paper was in preparation, a multicentre study from the USA further showed that the distinction between favourable (CPG2) and unfavourable (CPG3) intermediate‐risk disease also has utility in distinguishing men with different risks of metastasis after radical treatment . Although AS was not explored in that study, it showed a starkly higher risk of metastasis at 10 years in men with CPG3 disease (10–13.5%) than those with CPG2 (0.2–3.5%) depending on the type of radical treatment.…”
Section: Discussionsupporting
confidence: 88%
“…The study by Berlin et al, which validated Zumsteg et al, included just 258 patients treated with brachytherapy (3). In this group, differences in biochemical recurrence and distant metastasis did not reach statistical significance between the favorable-IR and unfavorable-IR groups, although events rates were low, with only 34 patients having a biochemical recurrence and 18 developing distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were based on 1,024 patients treated with doseescalated external beam radiotherapy (EBRT), and the classification was incorporated into the 2019 NCCN guidelines. Berlin et al validated the sub-classification using an international multi-institutional cohort of 2,550 patients treated with EBRT, radical prostatectomy, and brachytherapy (3). However, there were only 258 (10%) patients in their cohort treated with brachytherapy.…”
Section: Introductionmentioning
confidence: 99%
“…We emphasize that the creation of risk groups or strata that are relevant to clinical practice is entirely feasible and appropriate once the fundamental components (including TNM categories, biological variables and others) are established. Composite risk or prognostic groups of this type are often helpful, although they also have limitations [35][36][37] . Such risk groups are usually not generalizable across the full spectrum of disease and tend to be specific to anatomy and time-dependent scenarios 21,[38][39][40] .…”
Section: Amalgamation Of Other Prognostic Factorsmentioning
confidence: 99%